2013
DOI: 10.1308/rcsann.2013.95.8.582
|View full text |Cite
|
Sign up to set email alerts
|

Managing supracondylar fractures of the distal humerus in children in a district general hospital

Abstract: INTRODUCTION Controversy exists regarding the timing of surgery in children with displaced supracondylar fractures of the humerus. METHODS We reviewed retrospectively the postoperative outcomes and complications in these children managed in a district general hospital. RESULTS There were 81 children with displaced supracondylar fractures (64 Gartland type III and 17 type IIA). Of these, 46 children were treated within 6 hours of presentation and 35 were treated later. The rate of open reduction was higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The eligible 49 studies all reported the proportion of cases with open and closed reduction 7,10,25-50,51-70 . The pooled overall proportion obtained for ORIF was 0.16 (95% CI = 0.14, 0.18; Table III; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The eligible 49 studies all reported the proportion of cases with open and closed reduction 7,10,25-50,51-70 . The pooled overall proportion obtained for ORIF was 0.16 (95% CI = 0.14, 0.18; Table III; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[5,14] Some studies that have evaluated outcomes and complications with respect to timing found no difference in the infection rate, neurovascular injury, length of hospital stay, or conversion to open reduction. [15][16][17][18] Others, however, recommended urgent fixation as any delays made the subsequent surgery difficult and raised the chances of complications. [19,20] In Ghana and most of the subregion, aside from patients with SCHF presenting late, others are taking to traditional bonesetters for management leading to permanent disability, and life and limb-threatening complications.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies that have evaluated outcomes and complications with respect to timing found no difference in the infection rate, neurovascular injury, length of hospital stay, or conversion to open reduction [15–18] . Others, however, recommended urgent fixation as any delays made the subsequent surgery difficult and raised the chances of complications [19,20] .…”
Section: Introductionmentioning
confidence: 99%